# Cscx-secx=0

## Simple and best practice solution for Cscx-secx=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Cscx-secx=0 equation:

Simplifying
Cscx + -1secx = 0
Reorder the terms:
-1cesx + csxC = 0
Solving
-1cesx + csxC = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), 'csx'.
csx(-1e + C) = 0
Subproblem 1Set the factor 'csx' equal to zero and attempt to solve:
Simplifying
csx = 0
Solving
csx = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
csx = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1e + C)' equal to zero and attempt to solve:
Simplifying
-1e + C = 0
Reorder the terms:
C + -1e = 0
Solving
C + -1e = 0
Move all terms containing c to the left, all other terms to the right.
Add '-1C' to each side of the equation.
C + -1C + -1e = 0 + -1C
Combine like terms: C + -1C = 0
0 + -1e = 0 + -1C
-1e = 0 + -1C
Remove the zero:
-1e = -1C
Add 'e' to each side of the equation.
-1e + e = -1C + e
Combine like terms: -1e + e = 0
0 = -1C + e
Simplifying
0 = -1C + e
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`